Optimization of Turning Parameters using RSM During Turning of AISI H11 with Dimple Textured Uncoated Carbide Tool (London Journal of Engineering Research, 2023)
In this study, an attempt is made to understand the performance of dimple textured uncoated carbide cutting tool during turning of AISI H11 hot die steel in dry environment. Response surface methodology (RSM) was adopted to evaluate the effect of turning process parameters (cutting speed 80-120 m/min, feed rate 0.16-0.32 mm/rev and depth of cut 0.2 -0.5 mm) on tool flank wear (VB) and surface roughness (Ra). The results of the experimental runs are examined using ANOVA and variable interaction plots. Flank wear initially less at lower cutting speed of 80 m/min but as the speed increases wear on flank increases with same trends of feed rate. At low feed rate of 0.16 mm/rev surface roughness is low at all cutting speeds, whereas with increase in feed rate deteriorate the surface quality. Similarly, with 0.2 mm depth of cut Ra is 2.23 µm and with increase in depth of cut value Ra approaches 2.98 µm. Optimization and modelling was conducted to minimize wear and roughness using 5% error. Confirmation of the test runs shows 3.84% and 4.47% error between predicted and experimental values of VB and Ra.
Keywords: textured tool; RSM; surface roughness; tool wear